TINDAK TUTUR EKSPRESIF DALAM NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY - Hanissa, Nevifah Bella; Riyadi, Sugeng (Universitas Hamzanwadi, 2022)
The novel Bidadari with Clear Eyes by Habiburrahman El Shirazy. This novel presents an interesting story about the lives of young people in a pesantren as a medium for researching expressive speech acts. The purpose of this study was to describe the types of expressive speech acts and expressive speech acts in the novel Bidadari Bermata Bening. This research uses descriptive qualitative research method. Data collection in this study is in the form of quotes between dialogues of the characters. In the types of speech acts in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy, 18 utterances of expressive gratitude were found with meaning as a form of help and expressive speech acts of praise as many as 13 utterances with meaning as a form of praise.Keywoards: Speech Acts, Expressive Speech Acts, Novels.